The effectiveness of family education classes on parental bonding and high-risk behaviors among adolescents - Esfandiar Ebrahimtabar Gerdroodbari; Seyedeh Olia Emadian; Bahram Mirzaeian (فصلنامه ابن سینا)
Background and aims: Adolescent period is associated with conflicting feelings, physiological and emotional stimuli, which causes conflicts in parent-adolescent relationships. The aim of this study was to determine the effectiveness of family education classes on parental bonding and high-risk behaviors among adolescents. Methods: The research was a quasi-experimental pre-test post-test study with a control group. The statistical sample of the study consisted of 30 female high school students in Babol city (in the academic year of 2019-2020) with high-risk behavioral problems and their mothers. The subjects were selected by purposive non-random sampling method and were randomly divided into two groups of 15 (experimental and control group). The experimental group received weekly the family education program in eight sessions of 120 minutes. Before and after the intervention, parental bonding questionnaire and risky behaviors questionnaire were performed in both groups. Data were analyzed by covariance test. Results: The results of this study showed that family education program increased parental bonding and reduced high-risk behaviors among adolescents (p<0.001). Conclusion: In summery, the study showed that family education classes can be useful in improving the problems of adolescents with high-risk behaviors.